2020
DOI: 10.25259/ijms_113_2020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of preventive procedures followed by the medical staff against covid-19 in the Syrian Arab Republic: A cross-sectional study

Abstract: Objectives: This study was oriented to investigate the current situation of Syrian medical staff working in different fields and their response regarding the preventive procedures. Material and Methods: Questionnaire was designed according to the World Health Organization guidelines and recommendations, addressing the preventive measures, which must be followed by healthcare workers to protect themselves and their community against COVID-19. The participation in the study was average as 1339 participants fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…[ 5 ] A large hospital-based study in Syria showed high compliance with protective measures by hospital staff which was due to the training provided and was more among doctors and nurses and lower among pharmacists. [ 22 ] Another factor could be related to inappropriate disposal of PPE by staff members, increasing the exposure of hospital and sanitary attendants who are tasked for their final disposal. However, the possibility of higher exposure to hospital and sanitary attendants at the community level is also a definite possibility.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] A large hospital-based study in Syria showed high compliance with protective measures by hospital staff which was due to the training provided and was more among doctors and nurses and lower among pharmacists. [ 22 ] Another factor could be related to inappropriate disposal of PPE by staff members, increasing the exposure of hospital and sanitary attendants who are tasked for their final disposal. However, the possibility of higher exposure to hospital and sanitary attendants at the community level is also a definite possibility.…”
Section: Discussionmentioning
confidence: 99%
“…The overall high rate of responses and results are certainly a good sign from the part of doctors expressing their readiness to fight against this pandemic.There are reports on the relatively good commitment of medical staff to the preventive measures that have been recommended by the WHO. 19 The variations between different categories were small and negligible. Residents were the category who responded comparatively less in number (and in the pass rate).…”
Section: Discussionmentioning
confidence: 97%
“…The Corona Virus Disease of 2019 (COVID- 19) and its impacts confronts all with unpredictable, disruptive situations which have changed daily lives, economies, political decisions and healthcare system. The healthcare workers are in the forefront of the battle to treat the patients as well to prevent the transmission, putting themselves at high risk.…”
Section: Introductionmentioning
confidence: 99%
“…According to WHO guidelines to avoid crowding in clinic locations and to maintain a physical distance of at least 1 m, about 25.8% of the participants plan appointments when there is only one patient in the waiting room [10]. Even though fever is the most typical symptom of COVID-19 (88.7%), only about 16.1% of participants measure patients' fever before they enter dental clinics.…”
Section: 6mentioning
confidence: 99%